PENGARUH STRUKTUR MODAL, LIKUIDITAS, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BEI - Galbanero, Samuel Ricky; Espa, Vitriyan; Fahmi, Muhammad (Jurnal Bina Bangsa Ekonomika, 2025)
This research aims to examine the influence of capital structure, liquidity, and profitability on the value of companies in the telecommunications sub-sector. The subjects in this study are telecommunication companies listed on the IDX in 2021-2023. The data collected using this purposive sampling technique was obtained as many as 45 samples from a total of 15 companies for 3 years. The results of this study show that the capital structure measured by DER has a negative value, the liquidity measured by CR has a negative value and the profitability measured by ROA also has a negative value which indicates that the three variables studied have no effect on the company's value